Report of the Working Group on Aluminium, Magnesium, Titanium, Vanadium and Gallium for VIII Five Year Plan Volume I Summary, and Recommendations - Planning Commission (Planning Commission, 1989)
To make a brief critical analysis of the world scenario of Non-Ferrous and other metals, including past performance and future forecast on availability of ores, concentrates, metals, semis etc. with price trends in the past and future forecast including on exploration/Mine development, smelters, and other related matters such as, environmental laws, likely shift in mine-Smelter-Semi-fabrication integration concept or otherwise, trading, etc.
Ministry of Steel and Mines (Department of Mines)
Government of India Planning Commission
Keywords: Preamble; Bauxite; smelter and carbon technology; bauxite processing and alumina production; Titanium Sponge; Vanadium and Gallium; Nalco; Miscellaneous; fabrication; Revolutionary